3-Bromopyruvate Impairs Mitochondrial Function in Trypanosoma cruzi - Rafaella Oliveira da Costa; Davi Barreto-Campos; Juliana Barbosa-de-Barros; Giovanna Frechiani; Luiz Fernando Carvalho-Kelly; Ayra Diandra Carvalho-de-Araújo; José Roberto Meyer-Fernandes; Claudia Fernanda Dick (Pathogens, 2025)
Trypanosoma cruzi is a kinetoplastid parasite and etiological agent of Chagas disease. Given the significant morbidity and mortality rates of this parasitic disease, possible treatment alternatives need to be studied. 3-Bromopyruvate (3-BrPA) is a synthetic analog of pyruvate that was introduced in the early 21st century as an anticancer agent, affecting the proliferation and motility of certain microorganisms. Therefore, this work aims to evaluate the role of 3-BrPA in the energy metabolism, proliferation, and infectivity of T. cruzi, with a primary focus on the mitochondrial state, ATP production, and the key glycolytic pathway enzymes. It was observed that mitochondrial function in 3-BrPA cells was impaired compared to control cells. Accordingly, cells maintained in control conditions have a higher intracellular ATP content than cells maintained with 3-BrPA and higher ecto-phosphatase activity. However, the 3-BrPA reduced ecto-nuclease activity and was capable of hydrolyzing 5′-AMP, ADP, and ATP. When we evaluated two key glycolytic pathway enzymes, glucose kinase (GK) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), we observed that 3-BrPA induced higher GAPDH activity but did not alter GK activity. The compensatory energy mechanisms presented in T. cruzi may influence the process of cell metabolism and, consequently, the functional infectious process, suggesting the potential use of 3-BrPA in future clinical applications for Chagas disease.